Degradability index of novel locally isolated white rot fungi on agroindustrial wastes for production of animal feed. - Tijani, Ismaila; Jamal, Parveen; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed (2009)
Increased disposal costs in many parts of the world due to increasing population have increased interest in utilization of agro industrial residues for value added products. Due to abundant availability, agro industrial residue can be harnessed biotechnologically as an ideal substrate for microbial processes for the production of value-added products. Efficient utilization of these agro industrial wastes, which are mostly lignocellulosic, will also solve pollution problems that do occur through their disposal. Most lignocellulosic wastes cannot be utilized efficiently by livestock due to low digestibility and poor nutrient content. White rot fungi are perfect degrader of cell wall constituents especially lignin and they can also improve the nutritive value of their substrate. Solid state bioconversion using two isolated white rot fungi (RO1 and RO3)and Phanerochaete chrysosporium were carried out on two agroindustrial wastes (Rice straw and Cassava peel) in a 15 days fermentation. The microbes were evaluated based on their percentage degradation of cell wall constituents, protein content and minimal loss in dry matter without nutrient supplementation. White rot fungi (RO1) gave the best lignin degradation for cassava peel with minimal loss in cellulose. Phanerochaete chrysosporium gave the best protein increase on rice straw.